Facile preparation, through Schiff base formation, of luminescent amphiphilic carbohydrate polymers with aggregation-induced emission characteristics for biological imaging. Issue 79 (11th August 2016) - Xue, Yun; Liu, Meiying; Huang, Hongye; Deng, Fengjie; Zeng, Guangjian; Wan, Qing; Liang, Shangdong; Zhang, Xiaoyong; Wei, Yen
Abstract : Luminescent polymeric nanoparticles with aggregation-induced emission characteristics were fabricated via formation of a dynamic Schiff base between amino group-containing AIE dye and oxidation starch in the presence of water. Abstract : Novel fluorescent amphiphilic copolymers were prepared via Schiff base condensation between an aggregation-induced emission (AIE) dye (named as PHE) with one amino group and oxidation starch (DAS) with aldehyde groups. The size, morphology, composition as well as optical properties of resultant PHE–DAS were characterized in detail by means of a number of techniques. To evaluate their biomedical application potential, their biocompatibility as well as cell uptake behavior were also determined. We confirmed that the PHE–DAS can readily self-assemble into core shell nanostructures and display good water dispersibility and strong luminescent emission. Furthermore, these AIE active luminescent polymeric microparticles (LPMs) exhibited negative toxicity towards A549 cells and desirable biological imaging properties. More importantly, many carboxyl groups were generated on the PHE–DAS LPMs, making them useful for further surface functionalization and drug delivery applications. Taken together, we have developed a facile strategy for fabrication of AIE active carbohydrate polymers, which exhibited great potential for biological imaging and drug delivery applications.